RESTORATIVE JUSTICE SEBAGAI BAGIAN DARI HAK ASASI MANUSIA UNTUK MEWUJUDKAN ULTIMUM REMEDIUM PADA SISTEM PERADILAN PIDANA INDONESIA - Laurensius Arliman S (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Abstract: This study examines Restorative Justice as a manifestation of human rights within the framework of ultimum remedium in the Indonesian criminal justice system. The restorative approach is understood as a paradigm that places victim recovery, offender accountability, and community participation at the core of criminal case resolution. This orientation differs from the retributive model, which primarily emphasizes punishment and retaliation. The human rights framework provides a normative foundation that every individual is entitled to dignified and proportional treatment, as well as access to substantive justice. The principle of ultimum remedium reinforces the idea that criminal law, particularly imprisonment, must be used as a last resort after other alternative mechanisms have been considered. Legal reform through the new Criminal Code reflects a more humane and responsive policy direction toward societal needs. The integration of Restorative Justice into the criminal justice system is expected to achieve a balanced protection of public interests, victim restoration, and the fair social reintegration of offenders. Keywords: Restorative Justice, Human Rights, Ultimum Remedium.